INFLUENCE OF PINEAL GLAND’S HYPOFUNCTION ON THE STRUCTURE OF VISCERAL ORGANS - Pshychenko, V.V.; Chebotar, L.D.; Larycheva, O.M.; Tsviach, O.A.; Anasevych, Ya.N. (World of Medicine and Biology, 2020)
The purpose of this work was to study the morphological and functional changes in the pineal gland, heart, stomach, lungs and intestines of rats in the conditions of the pineal gland’s hypofunction. The studies were carried out on 24 sexually mature male Wistar rats, which were kept in standard vivarium conditions with round-the-clock lighting for 30 days. As a result of the performed microscopic studies, it was found that the lack of melatonin is accompanied by erosive gastritis with atrophy of the glands, an increase in proliferative activity and in the number of pathological mitoses in the jejunum of rats, which may indicate the genesis of malignant tumors. Dystrophies, atrophy and hypertrophy of cardiomyocytes, foci of cardiomyocytes’ lysis, circulatory impairment and inflammatory changes in lung tissues, which can be considered moderately expressed intestinal pneumonia, were revealed.
Keywords: pineal gland; pinealocytes; hypofunction; cardiomyocytes; intestinal pneumonia; gastritis